2001
DOI: 10.1149/1.1369372
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Low-k Silica Film Incorporated with Methylene Groups

Abstract: We have successfully demonstrated chemical vapor deposition of a silica film in which some of oxygen atoms of the pure silica network are replaced to methylene (-CH 2 -) groups. The as-deposited film was thermally unstable owing to the unwanted decomposition reaction of the methylene group with the dense H 2 O in the film. It was found that the film could be dehydrated without decomposition of the methylene group by low temperature annealing in a XeF 2 ambient. The dehydrated film showed not only good insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…This is also the evidence of the scission of Si-CH 3 and C-H bonds. Additionally, the appearance of peak at around 1360 cm −1 indicates the formation of Si-CH 2 -Si structure [25]. As previously reported [18,19,24], the formation of Si-CH 2 -Si structure is a radical reaction through the cleavage of Si-C and C-H bonds.…”
Section: Thermal Degradation Of Silicone Resin Containing Silphenylensupporting
confidence: 71%
“…This is also the evidence of the scission of Si-CH 3 and C-H bonds. Additionally, the appearance of peak at around 1360 cm −1 indicates the formation of Si-CH 2 -Si structure [25]. As previously reported [18,19,24], the formation of Si-CH 2 -Si structure is a radical reaction through the cleavage of Si-C and C-H bonds.…”
Section: Thermal Degradation Of Silicone Resin Containing Silphenylensupporting
confidence: 71%
“…Other authors have reported that methylene bridges [i.e. SiCH 2 Si and Si(CH 2 ) 2 Si] improve film mechanical strength and thermal stability 14–17…”
Section: Resultsmentioning
confidence: 99%
“…8, the vibrational spectrum of the asdeposited samples exhibits several peaks. 34 Stapinski et al 1,10 mentioned that the in case of low concentration of carbon the appearing band at 682 cm −1 ͑in the case of 600°C annealed sample͒ is due to the SiH x wagging mode and the bands at 742 cm −1 , which are assigned to Si-CH 3 rocking/wagging mode or to Si-C stretching mode 41,42 has the tendency to shift toward the higher wave number as the carbon concentration increases in the deposited film. On the other hand the most of the corresponding peaks disappeared after annealing of the sample at 600°C.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%